2021
DOI: 10.2991/aebmr.k.210218.012
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Economics With Education in Indonesia and Its Impact on Economical Building

Abstract: The research aims to find the relation between economics with education in Indonesia and its impact on economic building. It is qualitative research by using a theoretical review approach. The data are taken from the Education in Law no. 20 of 2003 concerning the national education system and some theories related to economy and education, then analyzed in the review forms of theory. The result of this research is education, and the economy in Indonesia are two interrelated sides. A strong economy is needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Investment in education has long been discussed in various studies [1][2][3][4][5], especially with interest that derives from the rate of return [6][7][8][9][10]. This is because the rate of return on educational investment is strongly related to the development and improvement of human resources that can promote the improvement of the country's economy [11][12][13][14][15], as the benefits of investing in education are not only income but also other broader benefits, such as more productive behaviour, healthy behaviour, and cultural behaviour [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Investment in education has long been discussed in various studies [1][2][3][4][5], especially with interest that derives from the rate of return [6][7][8][9][10]. This is because the rate of return on educational investment is strongly related to the development and improvement of human resources that can promote the improvement of the country's economy [11][12][13][14][15], as the benefits of investing in education are not only income but also other broader benefits, such as more productive behaviour, healthy behaviour, and cultural behaviour [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…With knowledgebased economy readiness (KKE), undergraduate students are expected to reduce unemployment as they can create their jobs with the knowledge they possess. Also, by preparing for a K-economy, undergraduate students can improve the quality of their human resources (Andrés et al, 2021;Kurniati et al, 2021). In addition, readiness to face economic challenges indicates whether students are ready to face the economy when it comes to their economic knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…They can solve social and environmental problems because student innovations can also help solve social and environmental problems, such as developing environmentally friendly technologies or solving public health issues. By preparing innovations, students can help create a stronger and more sustainable K-economy in the future (Kurniati et al, 2021;Weiss & Barth, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…USAID has worked for Indonesia to help transform generations of Indonesian families and communities through education and economic development [24]. The link between education and economic growth is critical to Indonesia's development, and investing in education can improve citizens' welfare, improve human capital, and achieve its economic growth goals [22], [23], [25].…”
Section: The Relationship Between Education and Economic Growthmentioning
confidence: 99%
“…A study found a negative and significant relationship between economic growth and income inequality in Indonesia [26]. Other studies emphasize the need for factors that can affect economic growth [25]. A research article analyzed income inequality and its impact on poverty through economic growth in Talaud Islands District [29].…”
Section: The Relationship Of Education and Income To Economic Growthmentioning
confidence: 99%